A Systematic Review and Meta-Analysis of Non-Antibiotic Agents in Comparison to Antibiotic Therapies for Prevention of Recurrent Urinary Tract Infection - Munawwir, Abdul; Syuaib, Achmad (Brawijaya Journal of Urology, 2025)
Introduction. Prolonged antibiotic usage can lead to modifications in the normal gastrointestinal tract and vaginal microbiome, which contributes to the UTI recurrence. This study aims to assess the impact of non-antibiotic therapies compared to antibiotic interventions in the prevention of recurrent urinary tract infections (UTIs). Methods. A systematic literature search was carried out from the PubMed, Google Scholar, Cochrane, and ScienceDirect databases published from 2013–2023, adjusted for inclusion and exclusion criteria. Keywords and Medical Subject Headings (MeSH) used were urinary tract infection, UTI, recurrent UTI, antibiotics, anti-bacterial agents, antimicrobial versus non antibiotic agents, probiotics, cranberries, D-mannose, vitamins, NSAID, prevention, treatment. The RevMan 5.3 program was used to analyze the risk of recurrent UTIs. Forest plot analysis was used to present relative risk estimates from individual studies and combined meta-analysis results. Results. Six studies were deemed eligible for quantitative synthesis and were included in this meta-analysis. This meta-analysis study showed a large heterogeneity, with p= 0.006 and I²= 85%. Pooled analysis using a fixed effect model showed the development of recurrent UTI was significantly lower in women with symptomatic UTI who were given non-antibiotic interventions compared to antibiotic interventions, with a relative risk of 0.75 (95% confidence interval (CI)= 0.61–0.92). This shows that non-antibiotic interventions significantly reduce the incidence of recurrent UTI compared to antibiotic interventions. Conclusion. Non-antibiotics interventions such as cranberry extract, D-mannose, NSAIDs, and herbal medicines can prevent recurrent UTI, and the results appear to be better or the same as antibiotic interventions. Meta-analyses should consider small numbers of studies with varying study designs and quality as well as small overall sample sizes.